THREE CASES OF ACUTE MESENTERIC LYMPHADENITIS DUE TO PASTEURELLA PSEUDOTUBERCULOSIS. Issue 5 (September 1960) - Mair, N. S.; Mair, Hélène J.; Stirk, E. M.; Corson, J. G.
Abstract : Seventeen cases of mesenteric adenitis were investigated between May and October, 1959, for the presence of virus as well as for evidence of Pasteurella pseudotuberculosis infection. Specimens examined included mesenteric glands, appendix, throat swab, faeces, and serum, although glands were received from only 12 patients. Virus was not isolated from any of the specimens, but evidence of infection with Pasteurella pseudotuberculosis was obtained in three patients. The three cases of acute mesenteric lymphadenitis due to Pasteurella pseudotuberculosis are reported. Pasteurella pseudotuberculosis Type IA was isolated from the mesenteric glands of two of the cases, and all three cases showed serological evidence of infection with the organism. The mesenteric glands of two of the cases showed histological changes characteristic of pseudotuberculosis.